Pengaruh Disiplin Kerja, Motivasi Kerja, dan Budaya Organisasi terhadap Kinerja - Widuri, Virsa Sari; Bernarto, Innocentius; Wuisan, Dewi (Sam Ratulangi University, 2020)
The objectives of this study are to find out whether: 1) work discipline has a positive effect on teacherâ€™s performance, 2) work motivation has a positive effect on teacherâ€™s performance, 3) an organizational culture has a positive effect on teachersâ€™ performance, 4) an organizational culture has a positive effect on work discipline, and 5) an organizational culture has a positive effect on work motivation. The research was conducted at the â€œXâ€ school in Tangerang Selatan using the census method and the Partial Least Square â€“ Structural Equation Modeling (PLS-SEM) tool to analyze the results taken from 42 respondents being censused. The findings concluded that the work discipline, work motivation, and organizational culture have a positive effect on the teachersâ€™ performance, and the organizational culture has a positive effect on work discipline as well as on work motivation of teachers in â€œXâ€ school. Â This research has contributed as an input for â€œXâ€ school to manage and maintain the schoolâ€™s culture which can improve the work discipline and work motivation of teachers, then it may lead to improved teacherâ€™s performance in order to achieve the schoolâ€™sâ€™s aim to provide quality education service.